Perancangan Cerita Bergambar Legenda Objek Wisata Goa Putri Menggunakan Gaya Paper Cut Digital - Vergiawan Aldrianto Putra; Hendra Afriwan (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
Books are one of the media that provide various information and knowledge on each page. Picture storybooks are among the most popular media for children because they contain interesting illustrations. Most regions in Indonesia have folklores or legends that contain strong local cultural elements, one of which is the legend of Goa Putri. At this time the legend of Goa Putri is conveyed through the signboard in front of the entrance to the Goa Putri Destination which has faded due to weather factors. In addition, the legend of Goa Putri is still conveyed orally by parents to their children from generation to generation without any supporting media. So the need for visual communication media to convey the legend of Goa Putri in the form of Pictures Book as a medium of information that can increase knowledge about existing local cultures. Therefore, this design is used to get a design concept and create a picture story based on the visualization of the legend of the Goa Putri the Paper Cut Digital style that applies Shading, silhouette style, Perception of depth and detailing. The method used in the design of the Glass Box method and for data analysis using the 5W + 1H method. In this design, in addition to the picture book as the main media, there are supporting media presented in the form of E-Book media, Paper Cut Shadow Box, Poster, Tote Bag, Pouch, Sticker, and Bookmark.